Exploring learners’ management of career-related transitions through career and self-construction - Cook, Antoinette (2015)
The purpose of my study is an exploration of the extent to which an intervention programme, based on career and self-construction, helps learners from diverse backgrounds manage career-related transitions. Two groups from two contrasting educational settings participated in a career intervention programme that is based on career and self-construction, and another two groups continued to participate in the standard, traditional Life Orientation lessons offered by their schools. A multilinear approach, with constructivism as the main theoretical framework, is utilised in developing the overall theoretical framework that underpins my research. A mixed method design that collects, analyses and reports on quantitative and qualitative data is used to provide in-depth answers to the questions I ask in my study. More specifically, in terms of the former data, a quasi-experimental, pre-test-post-test comparison group design using the results of the Career Adapt-Abilities Scale (CAAS) (Savickas, 2011d; Savickas & Porfeli, 2012), is employed. Responses from focus group interviews and reflective journals constitute the qualitative data. In terms of the quantitative data, the results suggest that the intervention programme did not improve participants’ career adaptability compared to the standard, traditional Life Orientation lessons as measured by the CAAS (Savickas, 2011d; Savickas & Porfeli, 2012). However, the qualitative findings indicate that my intervention programme enhanced the career adaptability skills in participants in the experimental groups from both schools. Overall findings suggest that participants from both schools benefitted from taking part in my intervention programme in terms of managing career transitions. === Thesis (PhD)--University of Pretoria, 2016. === Educational Psychology === Unrestricted